The Effect of Career Development and Organizational Commitment on the Motivation of Civil Servants at the Inspectorate of West Kalimantan Province - Anisa Susanti; Arninda Arninda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of career development and organizational commitment on the work motivation of Civil Servants (PNS) at the Inspectorate of West Kalimantan Province. The study employs a quantitative approach with an associative method. The research population consists of all Civil Servants at the Inspectorate of West Kalimantan Province (excluding the Inspector), totaling 114 individuals. The sample comprises 114 respondents selected using a saturated sampling technique. Data analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that all instrument items are valid and reliable. The regression model yields the equation Y = 1.139 + 0.310X1 + 0.341X2. The correlation coefficient value is 0.615, indicating a strong relationship between career development and organizational commitment and work motivation. The coefficient of determination is 0.379, meaning that 37.9% of work motivation can be explained by career development and organizational commitment, while the remaining 62.1% is influenced by other variables not included in this study. The simultaneous test results show a significant simultaneous effect of career development and organizational commitment on work motivation. The partial test results indicate that career development has a significant partial effect on work motivation, and organizational commitment also has a significant partial effect on the work motivation of Civil Servants at the Inspectorate of West Kalimantan Province.